EAU–ESMO consensus statements on the management of advanced and variant bladder cancer—an international collaborative multi-stakeholder effort: under the auspices of the EAU and ESMO Guidelines Committees. (19th November 2019) - Horwich, A; Babjuk, M; Bellmunt, J; Bruins, H M; Reijke, T M De; Santis, M De; Gillessen, S; James, N; Maclennan, S; Palou, J; Powles, T; Ribal, M J; et al.
Abstract: Background: Although guidelines exist for advanced and variant bladder cancer management, evidence is limited/conflicting in some areas and the optimal approach remains controversial. Objective: To bring together a large multidisciplinary group of experts to develop consensus statements on controversial topics in bladder cancer management. Design: A steering committee compiled proposed statements regarding advanced and variant bladder cancer management which were assessed by 113 experts in a Delphi survey. Statements not reaching consensus were reviewed; those prioritised were revised by a panel of 45 experts before voting during a consensus conference. Setting: Online Delphi survey and consensus conference. Participants: The European Association of Urology (EAU), the European Society for Medical Oncology (ESMO), experts in bladder cancer management. Outcome measurements and statistical analysis: Statements were ranked by experts according to their level of agreement: 1–3 (disagree), 4–6 (equivocal), 7–9 (agree). A priori (level 1) consensus was defined as ≥70% agreement and ≤15% disagreement, or vice versa. In the Delphi survey, a second analysis was restricted to stakeholder group(s) considered to have adequate expertise relating to each statement (to achieve level 2 consensus). Results and limitations: Overall, 116 statements were included in the Delphi survey. Of these, 33 (28%) statements achieved level 1 consensus and 49 (42%) statements achieved level 1 or 2 consensus. At the consensus conference, 22 of 27 (81%) statements achieved consensus. These consensus statements provide further guidance across a broad range of topics, including the management of variant histologies, the role/limitations of prognostic biomarkers in clinical decision making, bladder preservation strategies, modern radiotherapy techniques, the management of oligometastatic disease and the evolving role of checkpoint inhibitor therapy in metastatic disease. Conclusions: These consensus statements provide further guidance on controversial topics in advanced and variant bladder cancer management until a time where further evidence is available to guide our approach.